Pengembangan Sistem Informasi Manajemen Biopori Berbasis Web Menggunakan Metodologi RAD untuk Meningkatkan Efisiensi Pengelolaan Sampah Organik - Putra, Made Wahyu Purnama; Paramitha, A.A. Istri Ita; Putri, I Gst. Agung Pramesti Dwi (Jurnal Algoritma, 2025)
This research develops a Website-Based Biopori Management Information System as an innovative solution to overcome organic waste management problems in Peliatan Village, Bali. The village faced challenges in monitoring the One Million Biopores program due to the absence of an effective monitoring system, low community participation, and the absence of a centralized recording mechanism. Using Rapid Application Development (RAD) methodology, the system was developed through four stages: requirements planning, user design, construction, and implementation. The system has key features such as biopori data recording, harvest schedule notification, educational blog, and waste bank management. Testing using the User Experience Questionnaire (UEQ) with 34 respondents showed positive results on the aspects of attractiveness, efficiency, and accuracy of the system. Although there were variations in the assessment of clarity and novelty, overall the system succeeded in providing a satisfactory user experience. The system is expected to increase the effectiveness of biopore management in Peliatan Village and become a model for the development of similar systems in other areas.